True Science for Government Leaders and Educators: The Main Cause of Global Warming - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2020)
Government leaders and educators ought to be able to rely on scientists to tell the truth about climate change, but science has been tainted by politics. Real science, unlike politics, is all about telling the truth, truth that is securely anchored to the properties of matter and radiation. The current, high-profile, politically-driven, climate-change debate centers on two disparate ideas, namely, either global warming is caused by carbon dioxide or is not occurring at all. Neither is correct. Evidence from World War II indicates that particulate pollution, not carbon dioxide, is the cause of global warming. The difference between daily high and nightly low temperature data, tracked over time over a large geographic area, provide evidence that global warming is in fact occurring, which is independent of carbon dioxide. Particles in the lower atmosphere (troposphere) are heated by solar radiation and by radiant heat from the Earth, and transfer that heat to atmospheric gases by molecular collisions. The resultant heating increases atmospheric temperature, and reduces the temperature difference relative to air near the surface, which reduces atmospheric convection, and concomitantly reduces convective heat transport from the surface. This is the mechanism whereby particulate pollution causes global warming.